Estimating Technical Efficiency and its Determinants in the Coconut Plantations: The Case of Kurunegala Plantations Limited, Sri Lanka - Samarakoon, S. M. M.; Gunarathne, L. H. P.; Weerahewa, J. (International Coconut Community, 2022)
This study estimated the Technical Efficiency (TE) of coconut production in Sri Lanka using the stochastic frontier production function procedure. Data on inputs and coconut production recorded by Kurunegala Plantations Limited from 2000 – 2018 were used for the analysis. The stochastic production frontier in Cobb-Douglas form and the inefficiency model were estimated by single-step Maximum Likelihood method using STATA 14 computer software package treating coconut yield as the dependent variable and fertilizer, rainfall, labor, chemicals, tractor hours, mulching harrowing/plowing, agro-ecological zones, education level of the managers and bearing coconut extent as independent variables. Results revealed that TE of coconut production ranged from 81-98%, with an average of 88%, indicating that there is scope for increasing the production by as much as 12% without increasing inputs and simply using a higher technology level. The outcome of the analysis shows that inorganic fertilizer, rainfall, labor, tractor hours, and mulching are kind positive and significant. In contrast, agro-chemicals such as weedicides, fungicides and pesticides and plowing/harrowing did not show a significant contribution to coconut production. In respect of the farm and farmer-specific characteristics, the size of the estate has a positive relationship with technical inefficiency, meaning that smaller estates are more efficient than larger estates. It also shows that the agro-ecological zones and educational level have no significant effect on the efficiency of coconut production. The results highlight the need for government and private sector assistance in improving the efficiency of smallholders and promoting access to productive inputs.